SOME PSYCHOLOGICAL FEATURES OF STUDENTS’ COMMUNICATIVE SKILLS IN THE CONTEXT OF SOCIOMETRIC STRUCTURING - Honcharuk, Nataliia; Onufriieva, Liana (PSYCHOLOGICAL JOURNAL, 2019)
The formation of communicative abilities and skills at universities is highlighted in the article. This problem is particularly important, since future professionals’ training should be supported by their communicative literacy, competence, effective information exchange at interpersonal interactions. The purpose of the experimental study was to analyze psychologically the formation of communicative needs, abilities and skills of students at universities. In order to achieve the set purpose, the experimental study were conducted that had three major phases: 1) division of students by sociometric categories (based on J.Moreno’s test); 2) determining the levels of communicative need formation at the representatives of different categories (according to Yu. Orlov’s test); 3) determining communicative abilities and skills of the representatives of the determined categories (by L. Mikhelson's test). According to the sociometric research results, the highest percentage choices are given to the students from the group of popular students (39.7%), which is a favourable factor for formed communicative and interpersonal relationships in the group. There are also a lot of unpopular persons (38.1%); they received less than half of all choices. A favourable tendency is the fact that the both groups have a low index of isolation (6.3%), which can be significantly reduced under the condition of properly organized psychological corrective work. The study of communicative needs, carried out with Y. Orlov’s test "Research on the need for communication", has shown that favourable tendencies were determined at 95.24% of the students, among which the average level of communicative need formation was shown by the largest number of the respondents (73.02 %), above average indicators were shown by 19.05% of the respondents and the high level was achieved by 3.17% of the students. On this basis, one can argue that the focus on communication is preserved among students. At the same time, there is a small number of students (4.76%) with unfavourable tendencies according to the test. Their level of communicative needs is lower than the average one. Such young people do not show a desire for community and cooperation, do not like to be among people and friends, participate in various events. The study investigating the students’ communicative skills on the basis of L. Mikhelson's test has shown that 39.7% of the respondents demonstrates competent behaviour and preferred to use competent statements during communicative interactions. At the same time, according to the research results, a significant number of students showed aggressive behavioural tendencies (38.1%) and there is a small percentage of the respondents who showed addictive behaviour (15.9%). In order to summarize the research results and to find out their correlations, the obtained data were analyzed statistically, to determine such statistics as the average arithmetic sample (X), the median (Me), the mod (Mo), the dispersion (Sx), the correlation coefficient (Rxy). One of the most important outcomes of the performed statistical analysis was correlations calculated by Pearson correlation formula. Interdependence was determined only by two pairs of variables: a) sociometric status and competent behaviour – the coefficient 0,3290 indicates a direct moderate correlation; b) sociometric status and aggressive behaviour – the coefficient (-0.3570) indicates a reverse moderate correlation. Consequently, the higher the social status is, the more developed the competent communication is revealed in the use of competent statements, and the lower are aggressive manifestations, the less aggressive statements are used. Further research perspectives consist in the development of psychological corrective programs for communicative skills and abilities for students with addictive and aggressive forms of behaviour.